Etude comparative des graines, gousses et infrutescens de populations de différentes espèces de trèfles spontanés en Algérie - Rachida I.; Abdelguerfi A. (Systèmes sylvopastoraux. Pour un environnement, une agriculture et une économie durables, 1995)
Aimed at characterizing genetic resources of fodder and pastoral interest from Algeria, a morphological study on pods, seeds and fruiting structures of 139 wild populations of 12 clover species was conducted. This study assessed the occurrence of wide variation both among and within species and contributed to a better characterization of the genetic resources. Particularly in Trifolium scabrum, T. campestre and T. resupinatum, distinct morphological types were found for fruiting structures, which could be categorised into already described forms in the species.
Réunion du Groupe de Travail Méditerranéen du Réseau Interrégional FAO/CIHEAM de Recherche et Développement sur les Pâturages et les Cultures Fourragères, 1995/05/29-1995/06/02, Avignon (France)